PERENCANAAN PENINGKATAN JALAN TEMBUS JL. AMBARAWA- JL. SOEKARNO HATTA, BAWEN, SEMARANG - Aprilia Fitri Nuryati Ningrum; Karib Wicaksono; Moga Narayudha; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2015)
Highway with it’s accessories are a mode of land transport infrastructure wich are essential to the flow of services and commodity that pass through the land. With the flow of commodity and services, it will affect the economic and social development around the existing road infrastructure. Semarang has a strategic location in the development of the Province of Central Java, because Semarang crossed by important lines that connect to the regional growth centers such as Semarang, Surakarta, and Yogyakarta and it’s location close to the capital city of Central Java Province, wich is the center of economic activity, governance, social and cultural areas in Central Java. However, various problems of traffic jam occurs in the area of Semarang, this requiring an improvement road planning that will be an alternative way into the city of Semarang. Passageway of Jl. Ambarawa- Jl. Soekarno Hatta located between Ambarawa and Bawen with land use as residential areas, schools, fields, and forests. The main problem that occurred in this passageway are a pretty damage road caused by overload traffic flow and also because of pavement over time factor and because of the road capacity doesn’t required yet to accommodate the current traffic load. The purpose and goal of this evaluation and improvement are to maximize road function as an alternative way, in the end it’ll support a movement that can achieve economic growth of the area as well as reduce the problem, with a longer design time. The results of evaluation for the existing roads are gives several factors to improvement road. Due to the improvement and widening of road, it is automaticaly should redesign the geometry. The entire analysis and engineering calculations are based on the Highways Regulations and Indonesian National Standard. The results of improvement design it is carried one step of planning to widen this road in 2016, for a Rengas-Bawen segment, Gembol-Doplang segment and Harjosari-Doplang segment now widened into 7 m, for Rengas – Bawen segment before was 5 m of lane, and was 3 m for Gembol-Doplang and Doplang-Harjosari, three of them are design with 2/2 undevided lane, with new shoulder width 1 m. Design pavement used flexible ones and for the existing pavement need overlay with thick layer of 7 cm using Laston MS 454. For widening used surface course with thick layer of 10 cm using Laston MS 454, for base course using a class A crushed stone with a thickness of 20 cm CBR 100% and the subbase course using class B gravel CBR 50% with thick layer of 12 cm and lied on subgrade form browny red silty clay with sand in CBR 6%. Hope that this evaluation and improvement design can provide comfort services to road users during the specified design time of 10 years with a plan of speed 50 km / hour and a maximum slope of 9%.